PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 016 KEMANG INDAH KECAMATAN TAMBANG KABUPATEN KAMPAR - Eva Devita; Hendri Marhadi; Lazim. N Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT Basically the goal of education IPS is to educate and the provide basic skill for students to self development according to their talents, interests, abilities and the environment, as well as a range of provision for students to continue their education to a higher level. The student’s IPS outcomes at fourth grade in elementary school 016 Kemang Indah Tambang sub-district academic years 2013/2014 in the odd semester is low. The purpose of this research is to increase the student’s IPS outcomes by using cooperative Think Pair Share (TPS) learning model in the fourth grade in elementary school 016 Kemang Indah Tambang sub-district in the odd semester academic 2013/2014, this research is action research class. The subject are fourth grade student’s elementary school 016 that totally is 20 who is 7 male students and 13 female students. The students are heterogenic in academic. This research is three cycles, the data technique is observation and test. The percentage of the students before using the model is 45%, is increased 55% in the first cycle and increase 65% in the second cycle and increase also 80% in the third cycle. The activities of teacher and students has increased, the averager teacher’s activity in the first cyle is 60,94 with category enough increase 75,01 with categorygood in the second cycle and increase also 87,51 with category very good in the third cycle. The conclusion is shown that cooperative Think Pair Share (TPS) learning model can increase the student’s IPS outcomes. Keywords: Think Pair Share (TPS), IPS learning outcomes